The Manila conference, 1954 versus the Bandung conference,1955: the United States, the cold war and the challenge of non-alignment - Mason, Richard (Penerbit UKM, 2011)
This paper discusses the convening of the Manila Conference of 1954 and the Afro-Asian Conference in Bandung in 1955, two iconic Cold War conferences relating to newly emerged regions in the post-war world. The Manila Conference created SEATO, a Western-sponsored military pact of Western and Asian powers which sought to contain communism in Southeast Asia in the wake of French military defeat in Vietnam. The Bandung Conference of 1955 aimed at fostering closer relations between the newly independent Third World nations. Indian Prime Minister Jawaharlal Nehru, impressed with Chinese moderation at the Geneva, attempted to use the Bandung Conference to lay firmer foundation for the PRC’s relations with its Asian neighbours and to affect a rapprochement between China and the United States. Drawing upon the United States’ foreign relations papers, this essay analyses the United States’ estimates of Asians’ reactions to the establishment of SEATO and discusses the American anxieties over the convening of the Bandung Conference. American officials, it seemed, have little faith that Afro-Asian leaders could hold their own vis-à-vis the communist at Bandung. They also feared that Bandung would eventuate in the formation of an anti-American and anti-white bloc within the UN. The paper concludes that Washington’s anxieties over Bandung proved largely unfounded